PD-L1 expression and its clinicopathological correlation in advanced esophageal squamous cell carcinoma in a Chinese population - Lulu Rong; Yong Liu; Zhouguang Hui; Zitong Zhao; Yueming Zhang; Bingzhi Wang; Yanling Yuan; Wenbin Li; Lei Guo; Jianming Ying; Yongmei Song; Luhua Wang; et al. (BMC, 2019)
Abstract Background Programmed death ligand 1 (PD-L1) is a ligand for the inhibitory programmed cell death protein 1 (PD-1), which are targeted by several anti-PD-1 and PD-L1 drugs for a variety of human cancers. However, only a few studies have evaluated PD-L1 expression in esophageal squamous cell carcinoma (ESCC) with a large Chinese cohort. Our present study is to evaluate the association of PD-L1 expression with clinicopathological features on ESCC. Methods Using tissue microarray and immunohistochemistry, PD-L1 expression on tumor cells and tumor-infiltrating immune cells was studied in 378 advanced ESCC patients without neoadjuvant chemoradiotherapy. Its correlation with clinicopathological parameters was analyzed. Results PD-L1 was expressed on 29.9% (113/378) ESCC tumor cells and 40.2% (152/378) tumor-infiltrating immune cells. PD-L1 expression in tumor cells was significantly correlated with age, degree of differentiation, T stage, N stage and metachronous hematogenous metastasis, and PD-L1 expression in tumor-infiltrating immune cells was significantly associated with N stage (P < 0.05). Patients with PD-L1 expression in tumor cells had poor disease-free survival (Hazard ratio [HR] = 1.436, P = 0.009). There was a positive association between tumor cells and tumor-infiltrating immune cells for PD-L1 expression (r = 0.16, P = 0.002). However, PD-L1 expression in tumor-infiltrating immune cells was not significantly correlated with disease-free survival and overall survival. Conclusions PD-L1 expression in tumor cells and tumor infiltrating immune cells is not only an indicator for immunotherapy, but also significantly related with age, differentiation, stage, metastasis and disease free survival.